Alginate-based coatings containing laurel and olive leaves extracts, nisin and PLA packaging as bio-based solutions for chicken breast meat preservation - Márcio Moura-Alves; José A. Silva; Alexandra Esteves; Miguel A. Cerqueira; Cristina Saraiva (Applied Food Research)
The development of eco-friendly packaging systems incorporating natural antimicrobial and antioxidant agents represents a promising approach to improve poultry meat preservation. This study investigates the effectiveness of sodium alginate-based edible coatings enriched with laurel (Laurus nobilis) and olive (Olea europaea) leaf extracts, as well as nisin, applied to chicken breast meat and packaged using polylactic acid (PLA) trays and films. Samples were stored at 4 °C for 13 days and analysed for, colour, lipid oxidation (TBARS), protein degradation (TVB-N), microbiological stability and sensory attributes. Samples treated with laurel and olive extracts demonstrated strong antioxidant activity. The use of laurel maintained thiobarbituric acid reactive substances (TBARS) and total volatile basic nitrogen (TVB-N) values within acceptable limits. Nisin coatings showed the greatest antimicrobial efficacy, significantly inhibiting Listeria monocytogenes by >5 log on the last day of storage. Generally, sensory analysis showed no significant differences for overall freshness attributes (OFA) between treatments over time. These findings support the integration of plant-derived bioactive compounds and biopolymer-based packaging as sustainable strategies for meat preservation.